Partial organic substitution for chemical fertilizer reduces N2O emissions but increases the risk of N loss through nitrification in Tibetan farmland - Xiaofang Huang; Chengqun Yu; Wei Sun; Peili Shi; Junxi Wu; Jialuo Yu; Jiabao Wang; Tao Mu (Scientific Reports)
Abstract The combination of organic fertilizers (OFs) and chemical fertilizers (CF) is a promising agricultural management strategy to improve soil fertility while mitigating N2O emissions in croplands. However, there is still lacking of in-depth understanding of the effects of different OF and CF blends on N2O emissions and the underlying drivers. To this end, we conducted a short-term soil incubation to address the influences of partial OF substitutions for CF, i.e., 40% substitution of compost (CP), Yak dung (YD), Qingke straw (QS), and sheep dung (SD) on the processes of nitrification and denitrification in sandy loam soils in the Lhasa Valley. We found that CP, QS, and SD reduced cumulative N2O emissions by 53.43%, 25.96% and 16.64%, respectively compared to pure chemical fertilizer (N), except YD caused a significant higher in total N2O emissions. Fertilization treatments primarily regulate potential N2O emissions by affecting denitrification processes. While ammonia-oxidizing archaea (AOA amoA) could be the main driver of nitrification, and nirS abundance explained most of the cumulative N2O emissions. In addition, NO3 −–N tends to accumulate in the farmland soils, indicating an increase in the risk of leaching and nutrient loss. Overall, soil N2O emission reduction was favored by applying partial organic fertilizer substitution especially after through compost. Co-composting of animal manure and crop residue has more impressive potential for mitigating farmland N2O emissions.